2018
DOI: 10.13189/ujer.2018.060828
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Anxiety May Represent Archers' Actual Autonomic Nervous System Activity But How: Moderating Role of Personality Traits

Abstract: Objective: In the present study we aimed to examine the relationship between competitive anxiety, autonomic nervous system activity represented by Heart Rate Variability (HRV) and respiration, and performance in novice archers. We also interested in whether neuroticism may be a factor with a potential to moderate the link among anxiety, autonomic activity and archers' performance. Methods: The sample included 39 novice archers ranging in age from 18 to 27. Participants first completed to anxiety and neuroticis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Both three- and five-factor personality models include neurotic traits, which are closely related to mental health, physical health, and quality of life ( Lahey, 2009 ); these traits affect the cognitive and physiological responses of athletes during competition ( Balyan et al, 2016 ) and predict negative mental health results together with serotonin transporter gene polymorphism and competition pressure ( Petito et al, 2016 ). When applied in the discussion of specific events, Dal et al (2018) reported that neuroticism regulates the prediction of somatic anxiety on the activity of the sympathetic nervous system before and during archery competition. Through applying the three-factor EPQ-RSC, this study found that there was no significant difference between the two groups in different dimensions (including neuroticism) of personality, which provided a basis for the follow-up study examining the effect of the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both three- and five-factor personality models include neurotic traits, which are closely related to mental health, physical health, and quality of life ( Lahey, 2009 ); these traits affect the cognitive and physiological responses of athletes during competition ( Balyan et al, 2016 ) and predict negative mental health results together with serotonin transporter gene polymorphism and competition pressure ( Petito et al, 2016 ). When applied in the discussion of specific events, Dal et al (2018) reported that neuroticism regulates the prediction of somatic anxiety on the activity of the sympathetic nervous system before and during archery competition. Through applying the three-factor EPQ-RSC, this study found that there was no significant difference between the two groups in different dimensions (including neuroticism) of personality, which provided a basis for the follow-up study examining the effect of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have shown no difference between the CSAI-2 and STAI in evaluating precompetition anxiety traced back from five days after the competition ( Wilson et al, 2000 ). Differences in personality, especially differences in the neuroticism dimension, also induce different effects on the experience and the level of deterioration due to anxiety ( Lahey, 2009 ; Balyan et al, 2016 ; Petito et al, 2016 ; Dal et al, 2018 ; Rocha and Osório, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, this is not the first time that no correlation was found between objective physiological activity and cognitive anxiety. Indeed, in [47], the authors found a stronger association between respiration rate and somatic anxiety instead of cognitive anxiety in archers with the highest level of neuroticism. Hence, the low scores on neuroticism, though correlated with anxiety level, were not elevated enough to enhance EDA lability, contrary to the findings of other research [26].…”
Section: Conscientiousness Correlates With Electrodermal Stabilitymentioning
confidence: 97%
“…The first one investigated the relationship between personality traits, anxiety and physiological arousal in athletes, and revealed that an athlete’s neurotic personality could influence their cognitive and physiological responses in a competition. Moreover, a study by Dal et al 32 revealed that neuroticism could moderate the relationship between anxiety and autonomic activity (respiration) before and during an archery competition.…”
Section: Introductionmentioning
confidence: 99%